Phonological patterns in standard colloquial Bangla and Netrokona Dialect - Mizan, Nuzhat (BRAC University, 2014)
This thesis report submitted in partial fulfillment of the requirements for the degree of Bachelors of Arts in English at the Department of English and Humanities of BRAC University, 2014.